The Descriptive Study on Students’ Reading Comprehension in Scanning Recount Text of The Eighth Grade Students at SMP N 1 Glagah in The 2013/2014 Academic Year - Subayil, Subayil (LUNAR, 2017)
Reading is a multileveled and interactive process in which readers contruct a meaningful representation of text using their schemata. While it has been known for some time that both content and formal schemata are necessary for complete understanding of written texts in a reader’s first language (L1), and has been suspected to be true in the reader’s second language (L2). The purpose of this thesis is twofold. The first, to give a brief overview of some of the literature that deals with scanning as the alternative technique to teach reading comprehension. The second goal, to disscuss the implemetation of scaaning in the reading class. This classroom action research was intended to comprehend students’ reading in scanning recount text at SMPN 1 Glagah in the 2013/2014 academic year. It was conducted at the eighth year students. The respondent oh this research was consisted of 54 students who cocsisted of each class of the eighth grade. This respondents were chosen becouse they were as example of sample to establish the technique had goal or not. Involving the English teacher's preparation, the instructional activities conducted by the teachers, the material or technique used in the teaching of reading comprehension, the evaluation reading comprehension, and other factors that students succeed in the reading comprehension. The instruments of collecting data used test and documentation. The reading comprehension focused in recount text which used scanning technique. The reading comprehension test was used to get primary data about the students’ reading comprehension of English passages. In the implementation to find the value of reading comprehension by scanning techinique for the first time was providing related question reading test of recount text. It was done to determine the value students reading comprehension by using that technique mentioned above. So that, it will be known later on how to comprehend reading text. In the evaluation, the researcher got the test score from the respondent or students. Based on the result, it be concluded that the reading comprehension by scaanning technique had side-effect to improve the reading ability students and help the students of the eighth grade at SMPN 1 Glagah who they got some reading test which focused in recount text.